The Influence Of Digital Marketing And Brand Image On Purchasing Decisions At The Indomobil Plaza Dealer In Indramayu - Griesthalia Cantik Lusyana; Ika Nurjannah Nurjannah; Ihya Raihan Izzuddin; May Dedu (Politeknik Siber Cerdika Internasional, 2024)
This study aims to explore the extent to which digital marketing and brand image impact purchasing decisions. The research employs a quantitative approach, collecting data through research instruments and analyzing it descriptively. A sample of 48 respondents was selected using the Slovin method, and SPSS 25 was used for data analysis, including validity, reliability, linearity, multicollinearity tests, and multiple linear regression analysis (t-test and F-test). The findings indicate that both Digital Marketing (X1) and Brand Image (X2) significantly and positively influence Purchasing Decisions (Y) at the Nissan Indramayu car dealership. Together, these variables explain 49.4% of the variance in purchasing decisions, suggesting that other external factors not included in the study may also play a role.